Pengaruh Latihan Bola Gantung dan Alat Bet Terhadap Kemampuan Hasil Servis Atas Double Event Sepaktakraw Pada Atlet Sepaktakraw Kabupaten Kudus 2024 - Mohamad Miftahul Ulum; Agus Raharjo; Mahenderan Appukutty; Adi S (Indonesian Journal for Physical Education and Sport, 2024)
This study aims to determine the effect of hanging ball and bet training on the ability of service results for double sepaktakraw events in Kudus Regency 2024 sepaktakraw athletes. The method used is the Matched Subject Design pattern experiment. Using total sampling with a sample of Kudus Regency sepaktakraw athletes totaling 20 athletes. This research instrument test uses instructions for the upper service skill test from Solomon. Data analysis techniques using calculations with the help of SPSS 25 using the paired sample t-test method with the provision of Sig. (2-tailed) value <0.05 then